A guerra em Maquiavel: por que[m] morrem os soldados nos campos de batalha? - Zorzo, Douglas Antônio Fedel (2019)
The “war” occupies an essential position in the constitution of Niccolò Machiavelli’s political thinking. Conflicts, in their most varied configurations and expressions, are recurrent and regular topics in the Florentine secretary’s sprawling corpus. In the arte dello stato the war, rather than an empty possibility, is a concrete and irrevocable threat. On the Machiavellian horizon, military activities appear as an omnipresent element. In light of this, the present work has the purpose of investigating the specific place that “war” occupies in its reflection. Our intention is to situate the way in which the Machiavellian writings interpret the military phenomenon, outlining the locus of this word, reconstructing its meaning, exploring its definitions, its forms of manifestation, and especially its implications in the political arena. Here two main guidelines structure our journey. In the first, we will seek to expose the way that the Secretary conceptually conceives the war. For this, in the first chapter of our thesis, we will try to make a definition for this notion, both in its internal developments – in civil wars – as external – in interstate wars. In the second, consequently, we will discuss how this understanding affects the political dynamics of principalities and republics, political regimes that mark the author’s intellectual history. Condensed in the question about why the soldiers sacrifice themselves on the battlefields, we will turn our attention to the peculiarities of the political, institutional, and procedural organization of these forms of government that attempt to constitute their own arms, and how each political constitution reflects on the motivations of their armies. Then, in the second chapter, we will endeavor to point out how this understanding of armed conflicts impacts at the Machiavellian princely theory. On the one hand, as an essential attribute for the formation of principalities; on the other, as an indispensable element for the maintenance of political structures, which will constrain the prince to establish a specific form of relationship with the people under his command. Finally, in the third chapter, we will evaluate how this same idea reverberates in Machiavelli’s republican considerations, in a practical and theoretical context. The preservation of the republics, by force of arms, will guide the Secretary to the definition of a specific political model capable of promotion the formation of his own armies to control the chaotic world of fortune: the popular republic. In these terms, the hypothesis that we will pursue is that this particular view of war has such influence on the Machiavellian universe that it acts as a conditioner for its political positions. The demand to face a context of action, in which conflicts between powers emerge as inevitable, installs the political agent, regardless of his princely or republican inclination, ahead of other impositions strictly political, which defines either his behavior in respect to the individuals over which they rule how sets out the observance of certain institutional mechanisms.